Qualidade de sementes crioulas de Phaseolus lunatus L. tratadas com óleos essenciais - Soares, Maria Geisa da Silva (2023)
The Phaseolus lunatus L. species, popularly known as fava beans, stands out for having high nutritional value from green, ripe or dry beans, and the husks are processed for use in animal feed, mainly in periods of water scarcity. The cultivation of lima beans is carried out mainly in the Northeast region of Brazil, through family farmers, who are responsible for the maintenance and conservation of seeds of creole cultivars. However, the incidence of pathogens in seeds has caused great losses, which may make planting areas unfeasible, forcing the search for control alternatives that do not harm man and the environment. Essential oils can be an alternative for seed treatment, replacing industrialized products. Its function in the metabolism of seeds is to improve the physiological quality and vigor, acting as a natural protection against the attack of phytopathogenic microorganisms, due to its antifungal action. , Sweetgrass, Eucalyptus and Basil in the control of pathogens and in the physiological quality of the seeds of creole varieties of fava bean at a concentration of 1%. 200 seeds per treatment were used for the sanity test through the incubation method in Petri dishes. The physiological quality of the seeds was determined based on the germination, emergence and vigor tests. For the germination test, the Germitest® paper roll method was used and for emergence, the sowing was carried out in a greenhouse. Gas mass chromatography was performed to determine the components of the essential oils used. The following genera of phytopathogenic fungi were identified in lima bean seeds: Aspergillus sp., Penicillium sp., and Fusarium sp. Essential oils have antifungal action on pathogens, in addition to increasing germination, emergence, length and dry mass of roots and shoots, emergence speed index, without interfering with the vigor of the seeds of the studied varieties.